Manajemen Kepala Sekolah dalam Meningkatkan Kinerja Guru dan Tenaga Kependidikan di MAN 1 Tanjungbalai - Shopiana, Shopiana (Penerbit Widina, Widina Media Utama, 2025)
This study examines the principal’s methods in improving the performance of teachers and educational staff at MAN 1 Tanjungbalai. The principal implements effective communication approaches, discipline reinforcement, and motivation to enhance collective responsibility for education. Through a familial approach and open discussions, the principal establishes harmonious relationships with teachers and educational staff while encouraging learning innovations by providing guidance, direction, and opportunities for competency development through training, Subject Teacher Consultation (MGMP), workshops, and seminars. To improve the performance of educational staff, the principal applies a two-way communication pattern based on openness and transparency. Information dissemination is carried out through various media, such as staff meetings, circular letters, data boards, oral announcements, and informal communication based on a familial approach. The principal also provides space for educational staff to give feedback and criticism to enhance administrative efficiency and educational services. Through these methods, the principal acts as a facilitator and motivator in creating a conducive work environment, leading to improved teacher and staff performance, ultimately contributing to better education quality at MAN 1 Tanjungbalai.ABSTRAKPenelitian ini membahas manajemen kepala sekolah dalam meningkatkan kinerja guru dan tenaga kependidikan di MAN 1 Tanjungbalai. Kepala sekolah menerapkan pendekatan komunikasi yang efektif, pembinaan kedisiplinan, serta pemberian motivasi untuk meningkatkan tanggung jawab kolektif terhadap pendidikan. Melalui pendekatan kekeluargaan dan diskusi terbuka, kepala sekolah membangun hubungan harmonis dengan guru dan tenaga kependidikan, serta mendorong inovasi pembelajaran dengan memberikan arahan, bimbingan, serta peluang peningkatan kompetensi melalui pelatihan, Musyawarah Guru Mata Pelajaran (MGMP), workshop, dan seminar. Dalam meningkatkan kinerja tenaga kependidikan, kepala sekolah menerapkan manajemen komunikasi dua arah yang berbasis keterbukaan dan transparansi. Penyampaian informasi dilakukan melalui berbagai media, seperti rapat dinas, serta komunikasi informal berbasis kekeluargaan. Kepala sekolah juga memberikan ruang bagi tenaga kependidikan untuk menyampaikan masukan dan kritik guna meningkatkan efisiensi administrasi dan pelayanan pendidikan. Dengan metode ini, kepala sekolah berperan sebagai fasilitator dan motivator dalam menciptakan lingkungan kerja yang kondusif, sehingga kinerja guru dan tenaga kependidikan meningkat, berkontribusi pada mutu pendidikan yang lebih baik di MAN 1 Tanjungbalai.